За „българските мозайки” и княгиня Венцислава-Виола в полската литературна и културна памет - Cимеонова-Конах Галя (Slavica Lodziensia, 2019)
The author analyzes the presentations of the Bulgarian theme in Polish poetry and the popular culture (historical spectacles about Princess Ventsislava Viola in the Opole region, Poland). In Polish historical memory, the story of the Bulgarian Princess Ventsislava Viola (?–1251), the wife of Duke Casimir I, has been preserved in the Annals of Jan Długosz (Ioannes Dlugossius, 1415–1480). Analysis of poetical works from the twentieth century by Tadeusz Różewicz, Anna Kamieńska, Jan Zych, Jan Śpiewak and other authors devoted to Bulgaria, considered in literary discourse, makes it possible to identify five codes of artistic interpretation: stone as the quintessence of Bulgaria, history and metaphysics, beauty, ancient and medieval archaeological monuments of the Bulgarian lands, the land of abundant harvest.